Ruining, demolition and regeneration in urban space: Sketching the research problem - Kaczmarek, Sylwia. Autor (IGiPZ PAN, 2019)
The paper is intended to examine fundamental research problems connected with two processes that currently feature in urban space: demolition and regeneration as well as relationships between them seen from the perspective of diverse conceptual and theoretical approaches debated in geographic urban studies. Regeneration understood as a sequence of planned actions is about the redevelopment of degraded urban areas. Its idea is to introduce spatial, economic, social, and cultural changes in these areas to restore their social attributes, such as: improved standard of living, sustainable positive relations among various user groups, improved comfort in using the areas, and elimination of the existing inequalities. Demolition of a city means destruction of its infrastructure leading to morphological, functional, social, and cultural transformations. Knowledge about the reasons, course and effects of demolition helps us decide what types of demolition best fit given circumstances and subsequently propose effective remedy measures. By identifying relationships between demolition and regeneration in contemporary cities we can learn more about both processes and, consequently, more efficiently modernise organisation of space and its arrangement to meet the needs and requirements of present and future users. In conclusion we propose research questions which delineate the direction of further interdisciplinary studies in this field.
24 cm
Keywords: city; urban studies; demolition; urban regeneration; organisation of space; living conditions; quality of life